As escolas do campo do Ceará e a BNCC: a estruturação dos currículos da educação do campo - Silva, Francisco Samuel de Sousa e (2022)
This dissertation analyzed the structuring of the curriculum of the Rural Schools in the State of Ceará based on their Pedagogical Political Projects - PPPs before the approval of the National Common Curricular Base - BNCC, by Resolution CNE/CP n.º 2, of December 22 de 2017. To carry out this study, bibliographical and documentary research was carried out; moreover, during its course, semi-structured interviews were carried out with the coordination of a rural school - Escola Filha da Luta Patativa do Assaré (Agrarian Reform Settlement School), with a person responsible for the education sector of the MST and a person responsible for Education do Campo da SEDUC/Ce. The data were analyzed using the method of dialectical historical materialism, having critical historical pedagogy as an educational perspective. The general objective of the research was: to analyze how the rural schools of the State of Ceará structure the curricula, with emphasis on Escola Filha da Luta Patativa do Assaré, in order to defend the specificities of Rural Education, in view of the prerogatives established by the BNCC , having as specific objectives to analyze the context of Brazilian education in the post-coup of 2016; understand the concepts and characteristics of Rural Education and rural schools and their specificities and Identify how the high schools of the agrarian reform settlements in the countryside of the State of Ceará structured their PPPS, given the specificities of Rural Education National Common Curricular - BNCC in Brazil. In order to understand the relationships and contradictions between rural schools and the BNCC, the neoliberal reforms imposed on Brazilian education in the post-coup of 2016 were analyzed - such as Escola sem Partido, the High School Reform and the BNCC - and their implications in Rural Education. We brought the guise - albeit succinctly - the opportunistic expansion of EaD in the face of the Covid-19 pandemic through the placebo of remote education, how this issue harmed rural schools, as capitalist merchants institutionalized the exploitation of education, treating it as good and service, and no longer as a right. We start from a theoretical foundation based on Caldart (2017; 2012a, 2012b); Frigotto (2017; 2010; 2003); Marx (2012; 2011; 2010; 1987); Nogueira (1993); Ponce (1998) and Saviani (2013; 2008; 2007, etc.); to have a critical overview of the socio-educational context in which the approval of the BNCC took place and to understand how the secondary schools in the countryside of the State of Ceará - of the Agrarian Reform Settlements, structured their curricula, in order to safeguard the specificities of Education do Campo in their settlements even before the BNCC grids galvanized by multilateral organizations. It was concluded that despite the imposition of the BNCC, Ceará's Campo de Educação do Campo schools were successful in building curricular alternatives expressed in their PPPs as a form of resistance not to be fully restricted by the BNCC. Using instruments such as the inventory of life and the integrating curricular components (PEP, OTTP, PSC), as pedagogical differentials.